2014
DOI: 10.1007/s11524-013-9864-1
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Analysis of Father–Son Relationships among HIV-Positive Young Black Men Who Have Sex with Men

Abstract: Young black men who have sex with men (YBMSM) are experiencing high and rising rates of HIV infection, more than any other age-risk group category in the USA. Contributors to HIV risk in this group remain incompletely elucidated. We conducted exploratory qualitative interviews with 20 HIV-positive YBMSM aged 17-24 and found that father-son relationships were perceived to be important sociocontextual influences in participants' lives. Participants discussed the degree of their fathers' involvement in their live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…It is important to examine and understand these needs because parents are considered the preferred source of health information among YMSM . A recent study found that positive parent–child relationships have the potential to attenuate YMSM's risk of contracting HIV …”
Section: Discussionsupporting
confidence: 90%
“…It is important to examine and understand these needs because parents are considered the preferred source of health information among YMSM . A recent study found that positive parent–child relationships have the potential to attenuate YMSM's risk of contracting HIV …”
Section: Discussionsupporting
confidence: 90%
“…Without a cohesive community in which they could be engaged, BMSM are more likely to internalize negative views about same-sex behavior (Kraft et al, 2000; Stokes amp; Peterson, 1998), they may remain “hidden” and not disclose their homosexual behaviors and/or HIV status (Lichtenstein, 2008; Woodyard et al, 2000), and they may engage in unhealthy behaviors that can undermine HIV prevention (Mamary et al, 2007; Williams et al, 2004; Wilson amp; Moore, 2009). Given this, many of the studies reviewed here emphasized a focus on resilient aspects of BMSM’s social identities and lived experiences (Arnold amp; Bailey, 2009; Balaji et al, 2012; Hawkeswood, 1996; Hussen et al, 2014b; Jeffries et al, 2008) and the potential for creating communities that can foster resilience (Arnold amp; Bailey, 2009; Arrington-Sanders, Leonard, Brooks, Celentano amp; Ellen, 2013; LeGrand, Muessig, Pike, Baltierra, amp; Hightow-Weidman, 2014; Mamary et al, 2007). …”
Section: Resultsmentioning
confidence: 99%
“…Research has suggested that SSA Black youth are less likely to disclose their same-sex attraction to father figures and fathers may be more likely to have negative reactions to such disclosure (Cramer & Roach, 1988; Savin-Williams & Ream, 2003; Voisin, Bird, Shiu, & Krieger, 2013). One reason may be because father figures are likely to introduce heteronormative scripts to adolescents that further isolate them and may exacerbate or attenuate sexual risk behavior (Hussen et al, 2014). …”
Section: Discussionmentioning
confidence: 99%